Management of Improving the Quality of Education Through the Independent Curriculum at SDN Gladak Anyar 2 Pamekasan - Tika Hestiarini Utami; Ali Nurhadi; Intan Dwi Permatasari; Ach Syafiq Fahmi (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this research is to investigate the management of educational quality improvement via the independent curriculum, specifically focusing on the project to strengthen the profile on Pancasila learners (P5). The research method used in this study is qualitative, namely a field study cunducted in SDN Gladak Anyar 2 Pamekasan. The findings of this research explain that the Strengthening Student Profile Project (P5) is an interdisciplinary learning approach that aims to analyse and provide solutions for the issues that arise in the surrounding environment. The management strategy for improving the quality of education that may be used by teachers is the POAC strategy (Planning, Organizing, Actuating, Controlling). The implementation of P5 in schools is also considered capable of enhancing the quality of education via four stages, namely the introduction stage, contextualization stage, culmination stage, and reflection stage.